PENGARUH INVENTORY TURNOVER (ITO), DEBT TO EQUITY RATIO (DER), RETURN ON ASSET (ROA), EARNING PERSHARE (EPS), DAN PRICE EARNING RATIO (PER) TERHADAP RETURN SAHAM PADA PERUSAHAAN FOOD AND BEVERAGE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sinaga, Ria Veronica (UNIKA Santo Thomas, 2019)
This study aims to determine the effect of Inventory Turnover (ITO), Debt to Equity Ratio (DER), Return On Assets (ROA), Earning Per Share (EPS), Price Earning Ratio (PER) to Stock Returns on registered Food and Beverage Companies on the Indonesia Stock Exchange. The benefit of research is to provide information material to investors in making investment decisions. The number of companies to be sampled is 10 Food and Beverage Companies, namely: PT. Akasha Wira International Tbk (ADES), PT. Tiga Pilar Sejahtera Food Tbk (AISA), PT. Cahaya Kalbar Tbk (CEKA), PT. Multi Bintang Indonesia Tbk (MLBI), PT. Multi Bintang Indonesia Tbk (MLBI), PT. Sekar Laut Tbk (SKLT), PT. Ultrajaya Milk Industry and Trading Company Tbk (ULTJ), PT. Prashida Aneka Niaga Tbk (PSDN), PT. Indofood Sukses Makmur Tbk (INDF), PT. Delta Djakarta Tbk (DLTA), and PT. Mayora Indah Tbk (MYOR). In this study, secondary data is used, namely the Financial Report of Food and Beverage Companies listed on the Indonesia Stock Exchange for the period 2012-2016 which can be accessed via the internet. The data analysis method used is multiple regression analysis. Based on the results of the study, the regression equation was obtained as follows: Return = - 42,736 + 0,731 ITO + 13,582 DER + 3,306 ROA - 0,003 EPS + 3,203 PER + e showed that the ITO variable had a positive and not significant effect, the DER variable had a positive and insignificant effect. ROA variable has a positive and significant effect, EPS variable has a negative and not significant effect, and PER variable has a positive and significant effect on stock returns. ITO, DER, ROA, EPS and PER simultaneously influence the stock return of hospitality service companies. adjusted R2 value of 0.164. This means that 16.4 percent of variations in stock return variables can be explained by variations in ITO, DER, ROA, EPS and PER variables while the remaining 83.6 percent is explained by other variables outside the model.